Relational development in children with cleft lip and palate: influence of the waiting period prior to the first surgical intervention and parental psychological perceptions of the abnormality - Grollemund Bruno; Guedeney Antoine; Vazquez Marie-Paule; Picard Arnaud; Soupre Véronique; Pellerin Philippe; Simon Etienne; Velten Michel; Dissaux Caroline; Kauffmann Isabelle; Bruant-Rodier Catherine; Danion-Grilliat Anne (BMC, 2012)
Abstract Background The birth of a child with a cleft lip, whether or not in association with a cleft palate, is a traumatic event for parents. This prospective, multidisciplinary and multi-centre study aims to explore the perceptions and feelings of parents in the year following the birth of their child, and to analyse parent-child relationships. Four inclusion centres have been selected, differing as to the date of the first surgical intervention, between birth and six months. The aim is to compare results, also distinguishing the subgroups of parents who were given the diagnosis in utero and those who were not. Methods/Design The main hypothesis is that the longer the time-lapse before the first surgical intervention, the more likely are the psychological perceptions of the parents to affect the harmonious development of their child. Parents and children are seen twice, when the child is 4 months (T0) and when the child is one year old (T1). At these two times, the psychological state of the child and his/her relational abilities are assessed by a specially trained professional, and self-administered questionnaires measuring factors liable to affect child-parent relationships are issued to the parents. The Alarme Détresse BéBé score for the child and the Parenting Stress Index score for the parents, measured when the child reaches one year, will be used as the main criteria to compare children with early surgery to children with late surgery, and those where the diagnosis was obtained prior to birth with those receiving it at birth. Discussion The mental and psychological dimensions relating to the abnormality and its correction will be analysed for the parents (the importance of prenatal diagnosis, relational development with the child, self-image, quality of life) and also, for the first time, for the child (distress, withdrawal). In an ethical perspective, the different time lapses until surgery in the different protocols and their effects will be analysed, so as to serve as a reference for improving the quality of information during the waiting period, and the quality of support provided for parents and children by the healthcare team before the first surgical intervention. Trial Registration ClinicalTrials.gov Identifier: NCT00993993.